The times are changing: workforce planning, new health-care models and the need for interprofessional education in Australia. Issue 4 (4th July 2019) - Thistlethwaite, Jill E.; Dunston, Roger; Yassine, Tagrid
ABSTRACT: Following a history of the Australian health system and funding models, we outline workforce issues, in particular, the lack of health professionals in regional locations. The role of the Australian government health departments in workforce planning is discussed. We describe research funded by the Commonwealth government focussing on the development of interprofessional education (IPE) for collaborative practice. New models of interprofessional care have been introduced to help tackle the population needs: in the Australian Capital Territory (ACT); HealthOne in New South Wales; health-care homes nationally; and partnerships between pharmacists and general practitioners in Victoria. Changes in care delivery necessitate innovations in health education, however how IPE is embedded in Australian health professional education still varies. There is a growing sense of an IPE community complemented by an interest in IPE from peak policy and workforce bodies. There are changes underway in health professional registration and accreditation that are likely to regulate shared and common learning to enable the continuous development of a flexible, responsive and sustainable health workforce. We conclude that there are significant opportunities for further development of IPE and collaborative practice as key strategies for adding to the ability of health systems to address individual needs in conjunction with aiming for optimal and universal health coverage.